Dopamine receptor drugs and their applications - Lane, J. Robert; Bonifazi, Alessandro (Handbook of Behavioral Neuroscience, 2025)
This chapter provides a broad overview of the clinical uses and pharmacology of drugs that target the dopamine receptors, including the use of dopamine receptor antagonists as antipsychotics and dopamine agonists for the treatment of the symptoms of Parkinson's disease. It discusses some emerging approaches to develop new dopamine receptor-targeted therapies such as the potential of dopamine D3 receptor antagonists for the treatment of substance use disorders and the potential of dopamine receptor allosteric modulators. Finally, it summarizes the progress being made around the development of new compounds and approaches for use in research with a particular focus on approaches to selectively target the individual receptor subtypes.